Adaptive Modulation and Coding Using Signal to Noise Ratio Switching Threshold - Jasman, Faezah (2009)
Orthogonal frequency division multiplexing (OFDM) is one of the key enabling technologies for fourth generation (4G) wireless system. It offers high data rate transmission with high spectral efficiency, immunity to multipath fading and simple implementation using fast Fourier transform (FFT). However inefficient utilization of the channel will result when OFDM system is designed for worst-case channel conditions. Thus adaptive transmission scheme that can be adjusted to channel conditions is one of the techniques to improve the performance of OFDM systems. In this thesis, three types of subband adaptive transmission scheme namely adaptive modulation (AM), adaptive coding (AC) and adaptive modulation and coding (AMC) based on SNR switching threshold are investigated. The performances of these systems are evaluated using an efficient adaptation algorithm. The efficient adaptation algorithm is based on the average value of the SNR of the subcarriers in the subband. First the performance of adaptive modulation using quadrature amplitude modulation (QAM) and phase shift keying (PSK) system are evaluated. The results obtained showed that a significant improvements in terms of bit error rate (BER), spectral efficiency and throughput can be achieved. To further enhance the system, convolutional coding is employed. However convolutional coding causes the maximum throughput to be limited. To solve this problem adaptive coding schemes which provides another area of flexibility is investigated. Finally the combination of adaptive modulation and adaptive coding is examined. Simulations results have shown that the performance of adaptive transmission schemes are superior compared to fixed (nonadaptive) transmission schemes. A high throughput performance can be achieved without sacrificing the BER. The performance comparisons of the proposed system with the conservative system showed that the proposed scheme is able to meet the BER target of 10-3 with a slightly better throughput performance around 0.3 Bps/Hz.